RESULTS OF SURGICAL TREATMENT OF PULMONARY ATRESIA WITH VENTRICULAR SEPTAL DEFECT AND MAJOR AORTOPULMONARY COLLATERAL ARTERIES - R. R. Movsesyan; G. M. Chizhikov; A. A. Morozov; A. A. Shikhranov; N. V. Antsygin; V. A. Bolsunovskiy; V. G. Lyubomudrov (Вестник хирургии имени И.И. Грекова)
This article presents the 14-year experience of surgical treatment of pulmonary atresia with ventricular septal defect and pulmonary collateral blood bed. The surgery of defect was performed on 32 patients and they were followed up. The individual and differential approaches should be used in the choice of surgical strategy. This approach is based on the state of pulmonary arterial and collateral beds. An integral criterion of assessment was the common neo-pulmonary arterial index with boundary measure equal 150 mm²/m². An application of given method allowed the performance of successful radical repair of defect in 15 patients, 4 patients having been operated in one stage. The rest of the patients had the appropriate staged interventions. The lethality consisted of 9,4%.